KNOWLEDGE SHARING PRACTICES IN THE ORGANIZATION - Khaddraa, Rajuli (Universiti malaysia sarawak (UNIMAS), 2011)
The purpose of this study is to explore knowledge sharing practices in the organization. A qualitative (using open ended questions) questionnaire was used to collect data. This is followed by an in-depth interview wherever necessary. Nine informants who were officers in the top and middle management of two public organizations were selected for the study. The study implicates that knowledge sharing is perceived to be very important by all informants. Both organizations often organize activities that encourage knowledge sharing among its members. Knowledge sharing activities either required employees to meet regularly through discussion, training or taking courses or through electronic communication media. Indeed, the study reveals that knowledge sharing can be promoted though simple activities like staff gathering and sport events. As far as contributing factors is concern, most of the informants highlighted that their organizational culture, technology and top management commitment and support plays very important roles. On the other hand the main inhibitor of knowledge sharing is the attitude of individuals (selfish, ego, prejudice, ignorance, etc.). In fact, new findings show that knowledge sharing helps the organization to strengthen its members' relationship, achievement of mission and vision as well as increase knowledge sharing spirit. Knowledge sharer is seen as persons who are friendly, generous, concern and humble. They have good communication skill, competent, and knowledgeable. The study also contributes to existing models as well as concept, methodologies and directions for future research.